A study between corporate social responsibility and company financial performance: evidence from 24 companies that listed in Bursa Malaysia / Rozita Ghafar - Ghafar, Rozita (Faculty of Business Management, 2017)
Nowadays, Corporate Social Responsibility (CSR) is increasing interest of Malaysian companies and become an important area of a modern corporate research theory. Besides, the development of CSR activities all over the world is remarkable even the conduction of this activity incur some cost. Moreover, the correlation between CSR and financial performance showing some conflict results because of little proof support that CSR and financial performance have positive relation. This paper seeks to find the relationship between CSR and financial performance. Besides that, this research also reviewed the growth of CSR and literatures which focused on studies that used stakeholder theory by taking 24 Malaysia listed companies from 5 different industries as a sample then used regression analysis to measure the link between their CSR and their financial performance. A result from this study, except implementing the social responsibilities to shareholders has outstanding optimistic impact on Malaysia listed companies’ financial performance and implementing social responsibilities to customers, creditors, shareholders and suppliers have relatively positive impact. For other stakeholders the implementations of social responsibilities to them have negative impact on Malaysia listed companies’ financial performance.